(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Structural design is the primary aspect of Civil Engineers and its analysis is backbone of Civil Engineering. The improper analysis and design leads to failure of structure resulting loss of life. To perform accurate analysis, the structural engineer is able to analyze the structure considering different constraints like to satisfy the serviceability and deformability etc., by following IS codes. Though conventional method is still practicing, our technology is upgrading equally or even more based on latest softwares due to time parameter.